SISTEM SMART GARDEN BERBASIS SENSOR KELEMBAPAN UNTUK EFISIENSI PENGELOLAAN AIR - Nilfred Patawaran; Efraim K. M. Mogogibung; Cessi Rumondor (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2024)
The main issue faced by farmers in Tagulandang District is limited access and efficiency in irrigation and fertilization of crops. To address this, the study proposes the implementation of automation technology enabling monitoring and control of agricultural land conditions. This research aims to design and develop a Smart Garden system capable of monitoring soil conditions and automatic control. The methodology includes system design, data collection, implementation, and testing phases. Findings indicate that sensor technology and automation in Smart Farming enhance efficiency and productivity of nutmeg farming in Tagulandang. Accurate soil moisture and pH sensors provide consistent data for monitoring. The automated irrigation and fertilization system efficiently manages water and fertilizer use, improving resource management and crop productivity. This study successfully implements a Smart Farming system with soil moisture, pH, and water level sensors to enhance efficiency and productivity in nutmeg farming in Tagulandang, SITARO. The automated system regulates irrigation and fertilizer application based on soil conditions without requiring internet connectivity. Results show improved resource utilization and increased crop productivity in challenging geographical conditions.